2011
DOI: 10.1149/1.3591110
|View full text |Cite
|
Sign up to set email alerts
|

Ion-Cut Transfer of InP-Based High Electron Mobility Transistors

Abstract: The ion-cut transfer of InP-based transistors onto sapphire via adhesive bonding was successfully demonstrated. In this study, high-speed modulation-doped field effect transistor layers, or MODFETs, were first epitaxially grown on InP bulk substrates. The MODFET layers were then transferred onto sapphire using one of three methods: (A) substrate removal through polishing and etching, (B) conventional ion-cutting, and (C) patterned ion-cutting or masked ion-cutting. Following layer transfer, transistors were fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…8 In previous experiments, we have shown that devices fabricated on ion-cut InP layers either function with undesired characteristics ͑photodetectors͒ or do not function at all ͑transistor͒. 9,10 Masked ion-cutting can mitigate implantation damage by protecting critical regions from impinging ions with a thick, removable mask. 11 These protected areas are transferred along with adjacent implanted areas during exfoliation.…”
mentioning
confidence: 99%
“…8 In previous experiments, we have shown that devices fabricated on ion-cut InP layers either function with undesired characteristics ͑photodetectors͒ or do not function at all ͑transistor͒. 9,10 Masked ion-cutting can mitigate implantation damage by protecting critical regions from impinging ions with a thick, removable mask. 11 These protected areas are transferred along with adjacent implanted areas during exfoliation.…”
mentioning
confidence: 99%